Madam snake white : a case study on virtual reality continuum applications for Singaporean culture and heritage at Haw Par Villa - Cai, Yiyu (2018)
In this article, we describe a project on the use of Virtual Reality Continuum (VRC) for applications in culture and heritage. Haw Par Villa, a local heritage site in Singapore, is selected to demonstrate the entire process of VRC-enhanced digitization from laser scanning to 3D mapping and to 3D prototyping, using Madam Snake White as an example. The objective of the research is to investigate an effective and integrated solution to developing VRC applications for culture and heritage. Efforts are made for fidelity in the 3D modeling of the existing heritage for multiple applications, with the aim to popularize them in a simple and effective manner. In particular, in the case of Madam Snake White, we investigate the feasibility and effectiveness of digitization, 3D mapping, and 3D printing. We also discuss the use of online and interactive Madam Snake White as VRC heritage. A small group of volunteers were invited to a trial and their feedback was positive. Future work includes the application of VRC-enabled heritage for humanities education in local schools.